2010
DOI: 10.1101/gad.1924910
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling regulates mitochondrial physiology and insulin sensitivity

Abstract: Mitochondria serve a critical role in physiology and disease. The genetic basis of mitochondrial regulation in mammalian cells has not yet been detailed. We performed a large-scale RNAi screen to systematically identify genes that affect mitochondrial abundance and function. This screen revealed previously unrecognized roles for >150 proteins in mitochondrial regulation. We report that increased Wnt signals are a potent activator of mitochondrial biogenesis and reactive oxygen species (ROS) generation, leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
205
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(223 citation statements)
references
References 42 publications
15
205
1
Order By: Relevance
“…Taken together, these findings support a model of adipogenesis in which sFRP inhibits Wnt signaling to suppress oxidative metabolism and stimulate adipocyte growth during obesity (23). Wnt signaling also regulates mitochondrial physiology and insulin sensitivity (20). Regulation of mitochondrial division is critical for normal cellular function.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Taken together, these findings support a model of adipogenesis in which sFRP inhibits Wnt signaling to suppress oxidative metabolism and stimulate adipocyte growth during obesity (23). Wnt signaling also regulates mitochondrial physiology and insulin sensitivity (20). Regulation of mitochondrial division is critical for normal cellular function.…”
supporting
confidence: 62%
“…Wnt signaling activates mitochondrial biogenesis, which in turn produces elevated levels of reactive oxidative species (ROS) and oxidative damage (20). This effect on mitochondrial function and ROS generation may likely be responsible for some of the major biological consequences of altered Wnt signaling (21).…”
mentioning
confidence: 99%
“…During the last several years, it has been shown that the development of brown fat tissue is also significantly inhibited by canonical WNT signalling (Kang et al 2005). However, it should also be mentioned that mitochondrial biogenesis itself was found to be increased in response to WNT molecules , Yoon et al 2010. In summary, these molecular, cellular and physiological findings clearly demonstrate a crucial role for WNT signalling in rodent and human white and brown adipogenesis.…”
Section: Wnt Molecules In the Determination Of Preadipocytesmentioning
confidence: 60%
“…Recently, abnormal mitochondria and endoplasmic reticulum were observed in the deep zone of OC cartilage [29]. The mitochondrial dysfunction could be partially explained by the altered Wnt signaling pathway observed in the OC-affected horses because this pathway is known as a key regulator of mitochondrial function [17,30]. Furthermore, Power et al [31] demonstrated by immunohistochemistry that sclerostin, a major inhibitor peptide of the canonical Wnt pathway signaling was increased in naturally occurring lesions of equine osteochondrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study is to compare in young OC-affected horses (between 8 to 12 months), the different expression of selected genes depending the joints involved. 30 Belgian Warmblood horses with osteochondrosis and 11 Belgian Warmblood horses free of osteochondrosis were included in this study. All horses were between 8 to 12 months old.…”
Section: Introductionmentioning
confidence: 99%